Design and evaluation of gapless curved scintillator arrays for simultaneous high-resolution and high-sensitivity brain PET. (26th November 2019) - Du, Junwei; Bai, Xiaowei; Liu, Chih-Chieh; Qi, Jinyi; Cherry, Simon R
Abstract: Brain PET scanners that simultaneously provide high-resolution across the field-of-view and high-sensitivity can be constructed using detectors based on SiPM arrays coupled to both ends of scintillator arrays with finely segmented and long detector elements. To reduce the dead space between detector modules and hence improve the sensitivity of PET scanners, crystal arrays with curved surfaces are proposed. In this paper, the performance of a proof-of-concept detector module with nine detector submodules based on SiPMs coupled to both ends of a curved LYSO array with a pitch size of 1.0  ×  1.0 mm 2 at the front-end and a length of 30 mm was evaluated. A simple signal multiplexing method using the shared-photodetector readout method was evaluated to identify the crystals. The results showed that all the LYSO elements in the detector module of interest could be clearly resolved. The energy resolution, depth-of-interaction resolution, and timing resolution were 14.6%  ±  3.6%, 2.77  ±  0.39 mm, and 1.15  ±  0.07 ns, respectively, obtained at a bias voltage of 28.0 V and a temperature of 16.8 °C  ±  0.2 °C.